Peran Strategi Self Management Team dalam Organisasi - Mufti Afif (Islamic Economics Journal, 2015)
Self- management strategy team became a popular part in management science where this strategy while able to provide education for every individual of the team work but also able to solve the problems in an effective and efficient organization. This strategy take in five skills owned by each individual, which is capable of solving problems, capable of taking decisions, utilizing the resources available, seek and provide information, interact with people (or groups), and act on the beneficial aspects. For a leader, this strategy will form the typical attitude that is; Relating, scouting, persuading and empowering. Nevertheless this strategy cannot be implemented in all the company’s organization, except for those which already familiar with the culture of decisionmaking by employees.